Ekosocializem kot alternativa - Kirn, Andrej (Teorija in praksa, 2014)
The historical role of capitalism is waning. The alternative can be found in ecosocialism, which is inevitable in social and ecological terms. It should be established at global level. The necessity of its world-wide establishment however does not exclude local, national and international protests leading to a global turnaround from neoliberal capitalism to ecosocialism. Different types of socialism were always characterised by the critique of existing society, the idea of a more just society as well as the means and methods to achieve such a society. With the October Revolution the idea of socialism moved to the practical level. The labour movement was primarily harmed by Stalinism. The prospect of a social revolution in the economically, scientifically and technologically developed Western world is related to the doctrine of revisionism and reformist position. "The third way" between socialism and capitalism cannot be achieved within the social market economy but only within the social system of ecosocialism, which combines the characteristics of a democratic-humane socialism on one hand and those of a capitalist social market economy on the other. Ecosocialism would thus be characterised by alternative structural reforms: plurality of ownership, preponderant share of property in the hands of the employees, direct democracy and the green development breakthrough. Ecosocialism is the third way. To pursue it the relation between a social protest movement and a political party is important. Neoliberal capitalism has a destructive influence on society and on nature. In accessing the possible environmental/ecological and socio-economic impacts it does not consider the precautionary principle.
Keywords: družba; Družbena gibanja; Ecology; Ekologija; krize; Neoliberalism; Neoliberalizem; Social movements; Socialism; Socializem; society